Railway transportation systems : design, construction and operation - Pyrgidis, Christos N. (Boca Raton : CRC Press, 2022)
"This comprehensive overview covers the entire range of railway passenger systems, from conventional and high-speed intercity systems to suburban, regional, operating on steep gradients, and urban ones. New material provides innovations in rail freight transportation, case studies, and an update of cutting-edge technologies"--
OCLC-licensed vendor bibliographic record.
Keywords: Railroads -- Design and construction; Railroad engineering; Transportation engineering; TECHNOLOGY / Engineering / Mechanical; TECHNOLOGY / Construction / General